Strategi PT Telekomunikasi Selular dalam Memasarkan Produk Indihome di Kota Mataram: PT Telekomunikasi Selular's Strategy in Marketing Indihome Products in Mataram City - Sudarwin; Suljatmiko; Pudji Astuti (Al-Gafari : Manajemen dan Pendidikan, 2026)
IndiHome is one of the products issued by PT Telekomunikasi Selular in Indonesia issued the IndiHome product consisting of in 2015, IndiHome has two functions namely self care which is equipped with order tracking, the purpose of this study is how is the Strategy of PT Telekomunikasi Selular in marketing Indihome Products in the city of Mataram? and How is the Marketing Strategy of IndiHome Products of PT Telekomunikasi Selular in the city of Mataram According to Islamic Economic Law Analysis?. The method used in field research with qualitative descriptive method, Data in this study consists of Primary Data and Secondary Data. The data management techniques used are observation, interviews and documentation. The results of this study indicate that: 1). The marketing strategy implemented by PT Telekomunikasi Selular in marketing Indihome products in increasing its sales volume uses a 4P marketing mix consisting of product, price, process, promotion. 2). That the marketing strategy of PT Telekomunikasi Selular in marketing Indihome products in marketing its products is in accordance with the principles of Islamic economic law.